Deposit, Lending and Recovery Performance of Pandyan Grama Bank, Tamil Nadu: An Analysis - Suresh, R. (Indian Journal of Finance, 2012)
Until recently, it is well known that agriculture is one of the most important industries and has been accepted as the back bone of the Indian economy. Nearly seventy per cent of its population lives in villages and agriculture is the primary occupation of about sixty to seventy per cent of the total population of India. Tamil Nadu is one of the southernmost states of India. Since independence, the Government of India has been extending its fullest effort for the development of agriculture and allied activities. It is needless to specify that adequate credit facility is highly essential for agricultural growth. The agricultural agencies formed with the concept of multi-agency approach include commercial banks and cooperative banks, and they were lacking in many ways and were not able to fulfill the regional and functional gap in the rural credit system. As a result of it, the regional rural banks were formed and were included in the multi-agency approach for rural credit delivery mechanism in the year 1975, by placing a bill in the Parliament by the then Government for the formation of regional rural banks. The goal was achieved and came into being with the name of Regional Rural Bank Act, 1976, to cater to the needs of credit of the rural poor people. The selected Grama Bank in Tamil Nadu was established in accordance with the Regional Rural Bank Act, 1976, on 09th March, 1977, with the motto "SERVE WITH A SMILE". It is one of the first and foremost Regional Rural Banks in India. It is a joint undertaking of the Government of India, Government of Tamil Nadu and Indian Overseas Bank (Sponsor Bank), with the share capital contribution in the ratio of 50:15:35 respectively. This paper attempts to analyze the deposit, lending and recovery performance of the selected sample.